EFFECT OF SPATIAL AUTOCORRELATION STRUCTURE OF EMPLOYMENT IN CENTRAL JAVA - Devi Sumayya Sara; Abdul Karim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Industry, agriculture and THR sectors are some of the leading sectors in Central Java . Central Java with thecapital city of Semarang City, is the third in Indonesia with the highest population in addition to West Java and East Java. Given the high population density and economic growth rate, it should also be followed by the sector's ability to absorb the available employment. Whereas in reality, the world of work or industry and professional associations often complain that the quality of staff (graduates) has not yet met the required skills demands (competencies). So the need for assessment of the absorption of employment from elementary school to upper for the planning of education system, so that education is more directed to education system oriented to the world of work appropriately and more efficiently with adequate amount and quality can absorbed. Data used in this research is observation data to Central Statistics Agency of Central Java and Ministry of Education and Culture of Central Java for the period of 2015. Observation unit in this research is cities in Central Java , the data used among others the amount of absorption Workforce in general with basic education background  toupper. In addition to employment data, data supporting factors such as workforce, industrial GDP value, agricultural GDP value, THR GDP value, and wage employment is also a research variable. The results of this study are the variables that significantly influence the model are the variables workforce, agricultural GDP value, THR GDP value, and wage employment. While significant variables have significant and significant influence in the spatial model are the variables workforce, industrial GDP value, agricultural GDP value, andTHR GDP value. Keywords: Employment, Spatial Autocorrelation